2011
DOI: 10.1166/jnn.2011.4295
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Photonic Nanojets from Microsphere Arrays by Femtosecond Laser Ablation of Thin Films

Abstract: By comparing finite-difference time-domain near field simulations and femtosecond laser ablation of thin films, we characterize in three dimensional-space photonic nanojets from microsphere arrays. We demonstrate periodic drilling of transparent films with thickness up to 100 nm (onto absorbing substrates) is feasible with 1-microm diameter silica spheres. Working with larger polystyrene spheres, the apparent increase of the propagation length of the photonic nanojets makes possible to drill films as thick as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…After the threshold value, there is no significant increment in the crater size further though fluence is increased for single and double shots (see figure 2a). This could be attributed to the self-limiting character of ablation experiment using particles as focusing element, as already reported in [13]. Indeed, since the particles are ejected by momentum transfer from the ablated species, the higher is the laser energy, the sooner is the particle detachment and the disappearance of the focusing power at the target surface.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…After the threshold value, there is no significant increment in the crater size further though fluence is increased for single and double shots (see figure 2a). This could be attributed to the self-limiting character of ablation experiment using particles as focusing element, as already reported in [13]. Indeed, since the particles are ejected by momentum transfer from the ablated species, the higher is the laser energy, the sooner is the particle detachment and the disappearance of the focusing power at the target surface.…”
Section: Resultsmentioning
confidence: 55%
“…We carried out FDTD calculations to predict the enhancement factor. Details on the calculation procedure can be found in [13]. The results are presented in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%
“…When modest energy laser pulses are used, only locations of the substrate at the touch of the photonic nanojets are modified [3][4][5][6]. Taking benefit of the selfassembly properties of microspheres, this way is used to produce directly a well-ordered array of nanobeams leaving behind periodic features with size on the order of 100 nm, depending on the material response [7][8][9]. As model systems, we prepare colloid array assemblies on oxidized Si substrates ( fig.…”
Section: Introduction and Methodsmentioning
confidence: 99%
“…The LB technique provides one of the few methods of preparing organized assemblies of monolayers, which are prerequisite in various applications where high-accuracy spatially resolved methods are needed [33]. Such monolayers made with transparent microspheres find applications in the structuration of bulk substrates, resulting in either nanohole or nanobump arrays [34][35][36][37][38][39], but have also been explored in the literature in the context of electronics, optics, microlithography, chemical sensors, and biosensors [32][33][34][35][36][37][38][39][40][41]. It has been demonstrated that properly coated nanoparticles can be organized at the air-water interface by using the same procedure.…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%